Structural basis for the inhibition of AKR1B10 by the C3 brominated TTNPB derivative UVI2008. (1st October 2017) - Ruiz, Francesc X.; Crespo, Isidro; Álvarez, Susana; Porté, Sergio; Giménez-Dejoz, Joan; Cousido-Siah, Alexandra; Mitschler, André; de Lera, Ángel R.; Parés, Xavier; Podjarny, Alberto; Farrés, Jaume
Abstract: UVI2008, a retinoic acid receptor (RAR) β/γ agonist originated from C3 bromine addition to the parent RAR pan-agonist 4-[( E )-2-(5, 6, 7, 8-tetrahydro-5, 5, 8, 8-tetramethyl-2-naphthalenyl)-1-propenyl]benzoic acid (TTNPB), is also a selective inhibitor of aldo-keto reductase family member 1B10 (AKR1B10). Thus, it might become a lead drug for the design of compounds targeting both activities, as an AKR1B10 inhibitor and RAR agonist, which could constitute a novel therapeutic approach against cancer and skin-related diseases. Herein, the X-ray structure of the methylated Lys125Arg/Val301Leu AKR1B10 (i.e. AKME2MU) holoenzyme in complex with UVI2008 was determined at 1.5 Å resolution, providing an explanation for UVI2008 selectivity against AKR1B10 (IC50  = 6.1 μM) over the closely related aldose reductase (AR, IC50  = 70 μM). The carboxylic acid group of UVI2008 is located in the anion-binding pocket, at hydrogen-bond distance of catalytically important residues Tyr49 and His111. The inhibitor bromine atom can only fit in the wider active site of AKR1B10, mainly because of the native Trp112 side-chain orientation, not possible in AR. In AKR1B10, Trp112 native conformation, and thus UVI2008 binding, is facilitated through interaction with Gln114. IC50 analysis of the corresponding Thr113Gln mutant in AR confirmed this hypothesis. The elucidation of the binding mode of UVI2008 to AKR1B10, along with the previous studies on the retinoid specificity of AKR1B10 and on the stilbene retinoid scaffold conforming UVI2008, could indeed be used to foster the drug design of bifunctional antiproliferative compounds. Graphical abstract: Highlights: The X-ray structure of human AKR1B10 with RARβ/γ agonist UVI2008 has been solved. C3 halogen addition to pan -RAR agonist TTNPB enables RARβ/γ and AKR1B10 selectivity. Selectivity of UVI2008 for AKR1B10 is facilitated by Trp112 native conformation.